ERBB2 mutation is associated with a worse prognosis in patients with CDH1 altered invasive lobular cancer of the breast - Ping, Zheng (Oncotarget, 2016)
E-cadherin (CDH1) is a glycoprotein that mediates adhesion between epithelial cells and also suppresses cancer invasion. Mutation or deletion of the CDH1 gene has been reported in 30–60% cases of invasive lobular carcinoma (ILC). However, little is known about genomic differences between ILC with and without a CDH1 alteration. Therefore, we analyzed whole genome sequencing data of 169 ILC cases from The Cancer Genome Atlas (TCGA) to address this deficiency. Our study shows that CDH1 gene was altered in 59.2% (100/169) of ILC. No significant difference was identified between CDH1-altered and -unaltered ILC cases for any of the examined demographic, clinical or pathologic characteristics, including histologic grade, tumor stage, lymph node metastases, or ER/PR/HER2 states. Seven recurrent mutations (PTEN, MUC16, ERBB2, FAT4, PCDHGA2, HERC1 and FLNC) and four chromosomal changes with recurrent copy number variation (CNV) (11q13, 17q12-21, 8p11 and 8q11) were found in ILC, which correlated with a positive or negative CDH1 alteration status, respectively. The prevalence of the most common breast cancer driver abnormalities including TP53 and PIK3CA mutations and MYC and ERBB2 amplifications showed no difference between the two groups. However, CDH1-altered ILC with an ERBB2 mutation shows a significantly worse prognosis compared to its counterparts without such a mutation. Our study suggests that CDH1-altered ILC patients with ERBB2 mutations may represent an actionable group of patients who could benefit from targeted breast cancer therapy.